2006
DOI: 10.1111/j.1346-8138.2006.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Papulonecrotic tuberculid with spontaneous remission

Abstract: We describe a 62-year-old Japanese woman who had skin lesions involving her extremities, chest and back that showed spontaneous remission. The skin lesions consisted of slightly atrophic scars and crusted, reddish or necrotic papules. A tuberculin test showed induration and bulla, which was regarded as strongly positivity. Histopathologically, a tuberculoid granuloma with necrosis was present in the upper dermis and the deep dermis, including the adipose tissues. Bacterial cultures were not positive from sputu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…However, several reports showed that a number of skin manifestations disappeared quickly without any anti-tuberculosis therapy, suggesting the patients had a high degree of immunity. [910] Nonetheless, most of the PNT patients generally have no tendency for spontaneous remission, and they usually receive some anti-tuberculosis therapy. We give the patients multi-drug anti-tuberculosis therapy, and they both have a prompt response to the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, several reports showed that a number of skin manifestations disappeared quickly without any anti-tuberculosis therapy, suggesting the patients had a high degree of immunity. [910] Nonetheless, most of the PNT patients generally have no tendency for spontaneous remission, and they usually receive some anti-tuberculosis therapy. We give the patients multi-drug anti-tuberculosis therapy, and they both have a prompt response to the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, se ha identificado DNA micobacteriano en hasta 80% de las biopsias cutáneas de pacientes con tubercúlide papulonecrótica. 1,2 El diagnóstico puede demorarse, dado que la tubercúlide papulonecrótica es infrecuente y puede no haber un foco abierto de tuberculosis. Aunque la histopatología y la prueba tuberculínica indican el diagnóstico, la respuesta al tratamiento es la confirmación definitiva.…”
Section: Discussionunclassified
“…Se propuso como explicación el alto estado inmunitario observado en estos pacientes. 1 Sin embargo, no se debe demorar el tratamiento antituberculoso en los enfermos con tubercúlide papulonecrótica. Puntos claves • Prueba de tuberculina fuertemente reactiva.…”
Section: Tratamientounclassified
“…Acid‐fast bacilli could not be demonstrated in any of the cases using Ziehl–Neelsen stain. In one with associated pulmonary tuberculosis, the penile lesions had subsided spontaneously before antituberculosis therapy (ATT), a recognized feature in some patients . The remaining 14 were given rifampicin, isoniazid, ethambutol, and pyrazinamide in the appropriate dose.…”
Section: Clinical Details Of Patients With Penile Tuberculosismentioning
confidence: 99%